Mechanism of Flux-flow Activation in C-axis oriented Bi2Sr2CaCu2O8+δ Thin Films - de la Cruz, C.; Guerra, L.; Sarmago, R.; Salvador, A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001))
-